ANALYSIS OF PROGNOSTIC RISK FACTORS OF BLOODSTREAM INFECTIONS IN BEIJING COMMUNITIES: A RETROSPECTIVE STUDY FROM 2015 TO 2019 - Yan Liu; Beichen Cui; Chunmei Pi; Xiaohong Yu; Zhiwei Liu; Xiang Li; Liping Ma; Cong Wang (Mediterranean Journal of Hematology and Infectious Diseases)
Objective: This study intends to investigate the prognostic risk factors of bloodstream infection in Beijing. Methods: This study is a clinical retrospective study. Patients with community-onset bloodstream infections (COBSI) who were admitted to the emergency department and inpatient department of Beijing Jishuitan Hospital from January 1,2015 to December 31,2019 were selected as the main research objects. According to whether the patient survives for 100 days or not, the patients are divided into survival group and death group. By analyzing the clinical data of the two groups of patients, the epidemiology, clinical characteristics, bacterial resistance and risk factors affecting the prognosis of the patients were analyzed. Results: A total of 446 patients with COBSI diagnosed by blood culture were included in this study, including 252 men and 194 women. According to 100-day survival or not, patients were divided into survival group and death group, of which 363 cases were in the survival group and 83 cases were in the death group. The results of this study show that solid tumors, combined septic shock, indwelling catheters and hemodialysis treatment are independent risk factors affecting the prognosis of COBSI patients. Reasonable initial antibiotic therapy is a protective factor affecting the prognosis of COBSI patients. Conclusion: Solid tumors, combined septic shock, indwelling catheters, hemodialysis treatment, Charlson score, APACHE II score and PITT score are independent risk factors affecting the prognosis of COBSI patients in Beijing, the capital of China, and reasonable initial antibiotic therapy is a protective factor affecting the prognosis of COBSI patients.